Preparation of Multiwall Carbon Nanotubes Embedded Electroconductive Multi-Microchannel Scaffolds for Neuron Growth under Electrical Stimulation. (28th March 2020) - Liu, Zhenhui; Yushan, Maimaiaili; Alike, Yamuhanmode; Liu, Yanshi; Wu, Shuo; Ma, Chuang; Yusufu, Aihemaitijiang
Abstract : Objectives . To prepare the conductive MWCNT (multiwall carbon nanotube)-agarose scaffolds with multi-microchannel for neuron growth under electrical stimulation. Methods . The scaffolds were produced by gradient freeze and lyophilization methods. The synthesized materials were characterized by SEM and near-infrared spectroscopy, and their microstructure, swelling-deswelling, conductivity, biocompatibility, and shape memory behavior were measured. A three-dimensional culture model by implanting cells into scaffolds was built, and the behaviors of RSC96 cells on scaffolds under electrical stimulation were evaluated. Results . The addition of MWCNT did not affect the pore composition ratio and shape memory of agarose scaffolds, but 0.025% wt MWCNT in scaffolds improved the swelling ratio and water retention at the swelling equilibrium state. Though MWCNTs in high concentration had slight effect on proliferation of RSC96 cells and PC12 cells, there was no difference that the expressions of neurofilament of RSC96 cells on scaffolds with MWCNTs of different concentration. RSC96 cells arranged better along the longitudinal axis of scaffolds and showed better adhesion on both 0.025% MWCNT-agarose scaffolds and 0.05% MWCNT-agarose scaffolds compared to other scaffolds. Conclusions . Agarose scaffolds with MWCNTs possessed promising applicable prospect in peripheral nerve defects.